Dactyloidites ottoi in shallow marine deposits of the Coris Formation, Miocene, Costa Rica - Aguilar, Teresita (2020)
Dactyloidites ottoi traces associated with medium grained, mature, siliceous sandstone facies, with planar and curved parallel lamination and HCS cross laminations were developed in shallow marine environments (upper shoreface) of the Coris Formation (Miocene). High-energy environmental conditions were caused by waves, storms, tides and currents. Episodic sedimentation with high-energy erosive events caused by storms alternating with low-energy deposition with organic matter input favored sediment rework by organisms. These ichnofossils are infrequent in the sedimentary record and they had not previously been reported in Costa Rica. They are constituted by elongated elements which radiate from a central shaft and create a series of rosetted or fan-shaped tiered galleries. The organism that created these structures is yet unknown, however, several studies coincide that it must have been a feeding fodichnia trace produced by a worm-like organism which is part of the Cruziana Icnofacies.